MODEL PROBLEM BASED LEARNING UNTUK MENUMBUHKAN KEMAMPUAN BERPIKIR KRITIS SISWA DI SEKOLAH DASAR - Ryky Mandar Sary, Djariyo, Ihtiya Kusuma Dewi (Universitas PGRI Semarang, 2015)
The purpose of this study was to determine the increase students' critical thinking skills mathematics courses before and after application of problem based learning model. This type of research is quantitative. Data in this study were obtained through the test of critical thinking skills with narrative form, documentation, and observation. The study design used is one group pretest-posttest design. Based on the analysis of research data after getting treatment with problem based learning model, showed an increase in students' critical thinking skills. T test coefficient of 6.0125 and the coefficient is significant at the 5% level, as obtained thitung> ttable ie t = 6.0125> table = 2.093. It can be concluded that there is an increase in students' critical thinking skills mathematics courses before and after application of problem based learning model.